Corporate Social Responsibility and Its Nexus with Financial Performance: An Emerging Market Perspective - Thomas NYAHUNA; Mishelle DOORASAMY (International Journal of Environmental, Sustainability, and Social Science, 2023)
The significance of corporate social responsibility cannot be underestimated. Corporate ignorers of CSR initiatives are likely to be punished by customers leading to an impact on corporate financial performance. The present work evaluated the nexus between CSR and financial performance of 42 Johannesburg Stock Exchange (JSE) listed mining companies. The study followed a quantitative research approach with a correlational non-experimental research design. Data were collected from 2013 to 2021. Financial performance was taken as the dependent variable proxied by return on equity, return on assets and earnings per share. The independent variable of this research consisted of CSR index based on the Boston College Carroll School of Management Center for Corporate Citizenship reports. The findings show that return on assets was positively and significantly linked to return on assets. Two financial performance measures (earnings per share and return on equity) displayed no significant relationship with CSR. It was concluded that if companies adopt the right CSR initiatives can increase financial performance. From a practical standpoint, this study contributes towards developing of CSR policies and as well function as a trigger for listed companies that they can improve financial performance from CSR.